DESAIN APLIKASI SIG UNTUK PELAYANAN JARINGAN PIPA PDAM ( Studi Kasus : Jaringan Pipa PDAM Demak ) - Arief Laila Nugraha; Hani’ah Hani’ah (TEKNIK, 2011)
Regional water treatment and supply company (PDAM) Demak city is water utility service provider for Demakpeople. This company is one of important regional state enterprise to increase income regional of Demak City.PDAM as companies service must be build up the system that can be satisfied his consuments. One of the systemis Geographics Information System (GIS) Pipeline Aplication. The system is integrate Global Positioning System(GPS) that can knows real position pipeline routes, and programming GIS application that can makes the systemcan be operated user easily. The goal of the system is can calls back geodata of pipeline that be needed forPDAM to serve his consuments and knows area that can be covered existing pipeline routes.